Structure of Vomeronasal Organ (Jacobson) in the Male Red Fox (Vulpes Vulpes) - Hamid Karimi; Belal Hassanzadeh; Nasser Razmaraii (Negah Institute for Scientific Communication, 2016)
Introduction: Most mammalians possess an accessory olfactory system, which its first part is called vomeronasal organ (VNO). In this research, we studied the structure of this organ in Azerbaijani red fox. Methods: Heads of 10 healthy male fox carcasses were collected from areas around Tabriz and transferred to the laboratory in frozen form or in fixative solution. Biometrical experiments were done, then the maxillary bones cut into 5 pieces, and the pieces decalcified and embedded in paraffin. Then, 7-μm tissue sections were stained with H&E, PAS, and Masson's trichrome methods and explored under light microscope. Results: Two ducts of VNO start at the roof of mouth, about 3.17±0.28 mm behind the central incisor teeth, extend back into 2 sides of nasal septum and end near the first or second premolar teeth. This organ is surrounded by a hyaline cartilage, which is C-shaped in the first pieces and transform to "J" shape structure toward the back. The lining epithelium of lumen changes from nonkeratinized stratified squamous epithelium near the valve to pseudostratified columnar in the posterior portions. Presence of bipolar neurons in epithelium of medial wall shows VNO sensory function of smelling. Lamina propria-tunica submucosa in most portions have many serous and mucous secretory units and composed of a loose connective tissue with numerous blood vessels, which secretes pheromone. Also, this is an erectile tissue that can function in association with flehmen reaction to push toward the sensory epithelium of VNO. Conclusion: Orifice of VNO of Azerbaijani red fox same more mammalian open in oral cavity. It has 2 type epithelial tissues in end region. Sensory epithelium indicates important role of this organ for received of Pheromones.